Improved accuracy and confidence with multiple‐lead recordings from a single‐lead mobile electrocardiographic device. Issue 9 (22nd August 2019) - Frisch, Daniel R.; Weiss, Max; Dikdan, Sean J.; Keith, Scott W.; Sarkar, Kumar
Abstract: Background: Mobile electrocardiograms (mECGs) utilizing smartphone applications are an emerging technology. Typically, a Lead I rhythm strip is recorded. However, interpretation can be difficult in patients with sinus rhythm and low amplitude P‐waves (SR‐LAP) or atrial flutter (AFL). We hypothesized that patients could independently obtain multi‐lead tracings using a commercial mECG device, and that cardiologists who interpreted the multi‐lead tracings would make more accurate diagnoses and have more confidence in their interpretation compared to a single lead only. Methods: Thirty sets of recordings were obtained from 10 patients with either SR‐LAP or AFL that was not apparent on Lead I on a standard ECG. Patients recorded Lead I, Lead II, and Lead V1 tracings using AliveCor's KardiaMobile mECG device. Twenty‐nine cardiologists reviewed each patient's Lead I tracing, multi‐lead tracings (Leads I, II, V1), and 12‐lead ECG. Accuracy was noted and each cardiologist rated their level of confidence in their interpretation. Results: All patients were able to record their own single and multi‐lead tracings. Single lead, multi‐lead, and the 12‐lead ECG yielded 36.4%, 84.3%, and 97.7% agreement with the established diagnosis, respectively ( P  < .01 for each comparison). Overall mean confidence scores (out of a score of 5) were 2.95, 3.50, and 4.47 for single lead, multi‐lead, and the 12‐lead ECG, respectively ( P  < .01 for each comparison). Conclusions: Patients were able to record their own multi‐lead mECG tracings. Compared to a single lead recording, multi‐lead mECGs significantly improved cardiologists' diagnostic accuracy and confidence in their interpretation approaching that of a standard 12‐lead ECG.